Educational intervention planning for children in foster care in Finland: A case study. Issue 2 (3rd April 2018) - Pirttimaa, Raija; Välivaara, Christine
ABSTRACT: Children in foster care may face difficulties during their school years. When it comes to academic achievement, there is reported low school performance and lower grades. However, school may be strong protective factor in difficulties if supports are individual. School-based interventions represent a possibility for supporting children whose home life may make them vulnerable. This discussion paper presents Finnish initiative, which is based on Skolfam® model used in several Nordic countries.